Nitric Oxide Is Protective in Listeric Meningoencephalitis of Rats - Remer, K. A. (American Society for Microbiology, 2001)
The bacterium Listeria monocytogenes causes meningoencephalitis in humans. In rodents, listeriosis is associated with granulomatous lesions in the liver and the spleen, but not with meningoencephalitis. Here, infant rats were infected intracisternally to generate experimental listeric meningoencephalitis. Dose-dependent effects of intracisternal inoculation with L. monocytogenes on survival and activity were noted; 10(4) L. monocytogenes organisms induced a self-limiting brain infection. Bacteria invaded the basal meninges, chorioid plexus and ependyme, spread to subependymal tissue and hippocampus, and disappeared by day 7. This was paralleled by recruitment and subsequent disappearance of macrophages expressing inducible nitric oxide synthase (iNOS) and nitrotyrosine accumulation, an indication of nitric oxide (NO(⋅)) production. Treatment with the spin-trapping agent α-phenyl-tert-butyl nitrone (PBN) dramatically increased mortality and led to bacterial numbers in the brain 2 orders of magnitude higher than in control animals. Treatment with the selective iNOS inhibitor l-N(6)-(1-iminoethyl)-lysine (L-NIL) increased mortality to a similar extent and led to 1 order of magnitude higher bacterial counts in the brain, compared with controls. The numbers of bacteria that spread to the spleen and liver did not significantly differ among L-NIL-treated, PBN-treated, and control animals. Thus, the infant rat brain is able to mobilize powerful antilisterial mechanisms, and both reactive oxygen and NO(⋅) contribute to Listeria growth control.